POLITENESS STRATEGIES OF THE MAIN CHARACTERS IN THE FAULT IN OUR STARS NOVEL - Dewanti, Meilina Putri (Sanata Dharma University, Yogyakarta, 2022)
This paper explored politeness strategies and resolved two research questions, namely what politeness strategies were applied by the main characters in The Fault in Our Stars novel and what factors influenced the use of politeness strategies by the main characters in the novel. Data, consisting of 263 utterances containing politeness strategies, were collected from The Fault in Our Stars novel and were analyzed using a document analysis method. Results showed that the main two characters, namely Augustus and Hazel, applied four politeness strategies, which were distributed as follows: positive politeness, as the most frequently-used strategy with a frequency of 100 utterances (38%), followed by off record, 59 utterances (22.4%), bald on record, 54 utterances (20.6%), and negative politeness, 50 utterances (19%). The strategies that were used by the two main characters were affected by two main factors, namely the payoffs and the circumstances or sociological variables.